Prevalence and clinical characteristics of left ventricular dysfunction among elderly patients in general practice setting: cross sectional survey. Issue 7180 (6th February 1999) - Morgan, S; Smith, H; Simpson, I; Liddiard, G S; Raphael, H; Pickering, R M; Mant, D
Abstract: Objective : To assess the prevalence and clinical characteristics of left ventricular dysfunction among elderly patients in the general practice setting by echocardiographic assessment of ventricular function. Design : Cross sectional survey. Setting : Four centre general practice in Poole, Dorset. Subjects : 817 elderly patients aged 70-84 years. Main outcomes : Echocardiographic assessment of left ventricular systolic function including measurement of ejection fraction by biplane summation method where possible, clinical symptoms, and signs of left ventricular dysfunction. Results : The overall prevalence of left ventricular systolic dysfunction was 7.5% (95% confidence interval 5.8% to 9.5%); mild dysfunction (5.0%) was considerably more prevalent than moderate (1.6%) or severe dysfunction (0.7%). Measurement of ejection fraction was possible in 82% of patients (n=667): in patients categorised as having mild, moderate, or severe dysfunction, the mean ejection fraction was 48% (SD 12.0), 38% (8.1), and 26% (7.9) respectively. At all ages the prevalence was much higher in men than in women (odds ratio 5.1, 95% confidence interval 2.6 to 10.1). No clinical symptom or sign was both sensitive and specific. In around half the patients with ventricular dysfunction (52%, 32/61) heart failure had not been previously diagnosed. Conclusions : Unrecognised left ventricular dysfunction is a common problem in elderly patients in the general practice setting. Appropriate treatment with angiotensin converting enzyme inhibitors has the potential to reduce hospitalisation and mortality in these patients, but diagnosis should not be based on clinical history and examination alone. Screening is feasible in general practice, but it should not be implemented until the optimum method of identifying left ventricular dysfunction is clarified, and the cost effectiveness of screening has been shown.